Organisational wrongdoing in cross-national perspective: culture, context and comparative theory - Mitra, Subrata Kumar; Valarini, Elizângela; Pohlmann, Markus (Political corruption and organizational crime, 2021)
People—entrepreneurs, corporate managers, candidates in intensely contested elections or for that matter, ordinary folks filling in their tax returns—go through fleeting moments of indecision about whether to comply with the norms of transaction or not, in their everyday lives. These momentary indecisions are part of our ‘conditioned reflex’ as members of society, citizens, buyers, sellers and consumers who make up the political process and the market. Fortuitously, most people, most of the time, choose to comply with the norms of orderly transaction, and in consequence, hold the potential threat of anarchy at bay.